Factors affecting non-aeronautic revenue in Indian airports: a focus group study of Indian PPP airports. (25th October 2022) - Damodaran, Akhil; Shree, Deep; Singh, Pushpendra Pratap; Sagar, Mahim; Dhingra, Tarun
The Indian aviation industry is advancing rapidly, and non-aeronautical revenues are a critical component of airport businesses. Therefore, airport operators must devise creative strategies to improve the share of non-aeronautical revenue in the Indian airport sector. The purpose of this study is to explore factors that impact the development of non-aeronautical revenue businesses in the context of the Indian airport sector. A qualitative focus group discussion was conducted in this study in which experts from the aviation sector were included. Based on the discussion, four broad themes that influence non-aeronautical revenue generation are namely, regulations, business models, products and customers. The results of the research indicated a necessity for the development of non-aeronautical sources of revenue and functions as the base for further exploration for not only the Indian aviation sector but also for other emerging economies struggling with similar issues.